"Just in the Need That I Saw": Exploring Black Male Teachers' Pathways into Teaching. Issue 5 (19th October 2020) - Brooms, Derrick R.
ABSTRACT: Calls for the increased recruitment of Black male teachers continue to abound in both education and popular discourse. An underpin of this call is the potential contributions that Black male teachers can make with Black male students by serving as critical institutional agents or even role models. Less attention, however, has been paid to Black men's orientations toward teaching and how they make sense of their work as teachers. Using a philosophy of Black education approach, the current study examines the teaching experiences of three Black male teachers with particular attention given to their pathways into teaching and their decisions to work at Padmore Academy (pseudonym), an all-Black male academy. My findings suggest that these Black men view teaching through a communal lens and identify teaching Black boys through a holistic and relational approach as a critical need in Black communities. More particularly, they identified entering the teaching profession as a "calling" and, in deciding to work at Padmore Academy with its all-Black male student population, as part of an educational movement that could repair, enhance, and strengthen various aspects of Black communities. Implications are provided for preservice teacher programs in supporting Black boys and men considering teaching.